Improvement of Artemisinin Production in Hairy Roots Culture of Artemisia annua L. by Staphylococcus aureus - E Bandeh-Ali; M Keyhanfar; G Asghari (Institue of Medicinal Plants, ACECR, 2013)
Background: Artemisinin is an important plant secondary metabolite with anti-malaria, anti-viral and anti-cancer properties. In recent years many efforts have been made to improve artemisinin production through plant tissue culture (such as hairy roots). Objective: In this study, the effects of Stephylococcus aureus on artemisinin production in hairy roots of Artemisia annua were investigated. Methods: Agrobacterium rhizogenes strains A7 and Ar318 were used for the root induction. Two explants types were prepared, the first was leaf explants cut from both side (explant 1) and the second was, stems which cut from node (explant 2). The bacterial suspensions (A7 and Ar318) were inoculated at the wounding site of explants 1 and node explants 2. Transgenic nature of hairy roots was confirmed by amplification of rolB gene in polymerase chain reaction (PCR). Gas chromatography (GC) was conducted to determine artemisinin production. Results: About 5 to 10 days after inoculation by A7, hairy roots were appeared at the wounding sites of explants 2. Strain Ar318 could not induce any hairy roots. Also, after treatment with Agrobacterium suspensions, hairy roots were not induced in the explants 1 and explants were necrotic. The artemisinin content in the hairy roots treated with S. aureus suspension was 0.063, 0.133, 0.046 and 0.043 mg/g DW, respectively. Conclusion: Results show that various factors such as type of explants and Agrobacterium strains were effective in hairy roots induction. It seems that Stephylococcus aureus is stimulating the production of artemisinin in hairy roots of Artemisia annua.